2017
DOI: 10.1177/0033294117727746
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cognitive Processing Therapy and Prolonged Exposure in the Department of Veterans Affairs

Abstract: Multiple randomized clinical trials have shown that cognitive processing therapy (CPT) and prolonged exposure (PE) are evidence-based treatments for posttraumatic stress disorder (PTSD). However, additional research should verify the effectiveness of CPT and PE in conditions more reflective of clinical practice. The present study evaluated the effectiveness of CPT and PE at reducing veterans' self-reported PTSD symptoms as measured by total scores on the PTSD Checklist (PCL). This study involved a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 96 publications
(226 reference statements)
8
32
0
Order By: Relevance
“…The finding of effectiveness in both treatments when two or more psychotherapies are compared is consistent with the larger body of effectiveness research (e.g. [11,[61][62][63] stressed in this sense the notion that the completion of a treatment by the patient predicts effectiveness regardless of the applied method. In Applied Neuroscience And Mental Health EASTPP our study principles of Short Term Psychodynamic Psychotherapy (STPP) were executed in a multi-modal inpatient group therapy including nonverbal psychotherapy modules of expressive therapies, such as art therapy, psychodrama and psychomotor-therapy along the lines of STPP.…”
Section: ………………………………………………………………supporting
confidence: 82%
“…The finding of effectiveness in both treatments when two or more psychotherapies are compared is consistent with the larger body of effectiveness research (e.g. [11,[61][62][63] stressed in this sense the notion that the completion of a treatment by the patient predicts effectiveness regardless of the applied method. In Applied Neuroscience And Mental Health EASTPP our study principles of Short Term Psychodynamic Psychotherapy (STPP) were executed in a multi-modal inpatient group therapy including nonverbal psychotherapy modules of expressive therapies, such as art therapy, psychodrama and psychomotor-therapy along the lines of STPP.…”
Section: ………………………………………………………………supporting
confidence: 82%
“…The present study analyzed potential demographic, treatment, and trauma-related predictors of variable response to CPT delivered at an outpatient VA Medical Center. Overall, the results provide further support for the effectiveness of CPT in complex and highly symptomatic veteran populations (Resick et al, 2015;Rutt et al, 2018;Voelkel, Pukay, Walter, & Chard, 2015), as a clinically and statistically significant linear reduction in PTSD symptoms was observed for the average veteran (also observed by Resick et al, 2008;Rutt et al, 2018;Stein et al, 2012). Further, significant variability in treatment response to CPT was observed.…”
Section: Discussionsupporting
confidence: 66%
“…those with a trauma-focus (Bisson et al, 2013;Bradley et al, 2005;Jonas et al, 2013)). This said, recent studies have found that those who attend more treatment sessions generally obtain more favourable outcomes (Holmes et al, 2019;Rutt, Oehlert, Krieshok, & Lichtenberg, 2018). More transparent reporting of dropout is required to explore this further.…”
Section: Main Findingsmentioning
confidence: 99%